2021
DOI: 10.1186/s13046-021-01827-8
|View full text |Cite
|
Sign up to set email alerts
|

YAP and endothelin-1 signaling: an emerging alliance in cancer

Abstract: The rational making the G protein-coupled receptors (GPCR) the centerpiece of targeted therapies is fueled by the awareness that GPCR-initiated signaling acts as pivotal driver of the early stages of progression in a broad landscape of human malignancies. The endothelin-1 (ET-1) receptors (ET-1R), known as ETA receptor (ETAR) and ETB receptor (ETBR) that belong to the GPCR superfamily, affect both cancer initiation and progression in a variety of cancer types. By the cross-talking with multiple signaling pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 130 publications
(228 reference statements)
0
25
0
Order By: Relevance
“… 7 , 8 In addition, the EDNRA/ET-1 axis participates in the reprogramming of tumor-associated immune cells, such as neutrophils, 9 dendritic cells (DC), 10 tumor-associated macrophages (TAM), 11 , 12 tumor infiltrating lymphocytes (TIL) 13 and regulates the communication between tumor cells and tumor microenvironment (TME). 14 The existing body of research on bladder cancer suggests EDNRA is one of immune function-related genes, and has the potential to assess prognosis and predict the efficacy of immunotherapy. 15 Wei et al observed that EDNRA expression can be downregulated by miR-200c in regulation of gastric carcinoma cells proliferation, apoptosis and invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 In addition, the EDNRA/ET-1 axis participates in the reprogramming of tumor-associated immune cells, such as neutrophils, 9 dendritic cells (DC), 10 tumor-associated macrophages (TAM), 11 , 12 tumor infiltrating lymphocytes (TIL) 13 and regulates the communication between tumor cells and tumor microenvironment (TME). 14 The existing body of research on bladder cancer suggests EDNRA is one of immune function-related genes, and has the potential to assess prognosis and predict the efficacy of immunotherapy. 15 Wei et al observed that EDNRA expression can be downregulated by miR-200c in regulation of gastric carcinoma cells proliferation, apoptosis and invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…YAP is not only a transcriptional coactivator of many target genes in the nucleus but also a key effector of the Hippo signaling pathway. As YAP can regulate cell proliferation, differentiation, and apoptosis, it can control the size of organs and prevent tumorigenesis [46]. After the Hippo pathway is activated by various extracellular signals, YAP is phosphorylated at serine/threonine residues, inactivated by cytoplasmic isolation, and finally degraded by the proteasome [45].…”
Section: Discussionmentioning
confidence: 99%
“…ET-1/ET-1R axis activation gives cells the potential to exert changes in cell fate and accomplish deleterious features [ 296 ]. ET-1 expression has been detected in numerous malignancies such as in advanced tumoral contexts [ 297 , 298 ], where elevated ET-1R indicated worsened prognosis [ 296 ].…”
Section: Et-1 Modulates Pain and Drug Sensitivitymentioning
confidence: 99%
“…ET-1/ET-1R axis activation gives cells the potential to exert changes in cell fate and accomplish deleterious features [ 296 ]. ET-1 expression has been detected in numerous malignancies such as in advanced tumoral contexts [ 297 , 298 ], where elevated ET-1R indicated worsened prognosis [ 296 ]. Within tumours, ET-1 generates signals which induce pro-survival transcriptional answers, securing tumoral cells from cancer therapy-induced apoptosis [ 297 , 299 , 300 ].…”
Section: Et-1 Modulates Pain and Drug Sensitivitymentioning
confidence: 99%